Pre-Trial Insolvency Prevention: Economic and Legal Analysis - IZUYMOV, Igor Vladimirovich; SADYKOVA, Hadiya Nurgalievna; KORENKOVA, Svetlana Ivanovna; KILIN, Petr Martemjanovich; SAMOYLOVA, Yana Victorovna; SHESTAKOVA, Vera Ivanovna (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
This paper analyzes the nature of pre-trial insolvency prevention of a business entity, reveals the content of this phenomenon, and studies the possibilities of its use to prevent existing negative consequences of the court procedures on insolvency in the economy. The article discusses the features of pre-trial insolvency prevention (bankruptcy) of business entities conducting business abroad, analyzes the Russian and international practice of the legal regulation of pre-trial prevention of bankruptcy. It is proposed to regulate the activity of domestic entrepreneurs in the field of pre-trial insolvency prevention of business entities at the legislative level.